Categorization of Natural Whistled Vowels by Naïve Listeners of Different Language Background - Meyer, Julien; Dentel, Laure; Meunier, Fanny (Frontiers in Psychology, 2017)
Whistled speech in a non-tonal language consists of the natural emulation of vocalic and consonantal qualities in a simple modulated whistled signal. This special speech register represents a natural telecommunication system that enables high levels of sentence intelligibility by trained speakers and is not directly intelligible to naïve listeners. Yet, it is easily learned by speakers of the language that is being whistled, as attested by the current efforts of the revitalization of whistled Spanish in the Canary Islands. To better understand the relation between whistled and spoken speech perception, we look herein at how Spanish, French and Standard Chinese native speakers, knowing nothing about whistled speech, categorized four Spanish whistled vowels. The results show that the listeners categorized differently depending on their native language. The Standard Chinese speakers demonstrated the worst performance on this task but were still able to associate a tonal whistle to vowel categories. Spanish speakers were the most accurate, and both Spanish and French participants were able to categorize the four vowels, although not as accurately as an expert whistler. These results attest that whistled speech can be used as a natural laboratory to test the perceptual processes of language.